A Design of Learning Activities That Created Students' Self-Regulated Learning through LMS Moodle - Usman, Estika Satriani; Zaim, M.; Ermanto; Walpita, Chandima Kumara; Etfita, Fauzul (International Journal of Language Pedagogy, 2024)
Current Learning systems have enabled students to construct their knowledge by themselves. However, using various LMS will cause different learning situations and experiences for students in learning. This study investigates the effectiveness of Moodle-based learning activities in fostering self-regulated learning (SRL) among undergraduate students. The research was conducted over 8 weeks with 100 participants, employing a mixed-methods approach that included pre-and post-surveys, learning analytics, and qualitative data from focus groups and interviews. The findings reveal significant improvements in key SRL components: goal setting, self-monitoring, self-evaluation, and time management. Quantitative data from the Motivated Strategies for Learning Questionnaire (MSLQ) showed statistically significant gains across all SRL dimensions (p < 0.01). Learning analytics indicated that student engagement increased, reflected in doubled login frequency, a 33.3% rise in task completion rates, and a 66.7% increase in time spent on learning tasks. Qualitative data supported these results, highlighting the positive impact of Moodle’s tools on students' autonomy, motivation, and reflective learning practices. The study concludes that Moodle-based activities can effectively promote SRL by providing structured, interactive, and reflective learning experiences. Recommendations are made for educators to integrate diverse Moodle activities that target different SRL components and for institutions to provide continuous support and infrastructure improvements.